Implementing routine outcome measures in child and adolescent mental health services: from present to future practice. Issue 2 (2nd March 2012) - Batty, Martin J; Moldavsky, Maria; Foroushani, Pooria Sarrami; Pass, Sarah; Marriott, Michael; Sayal, Kapil; Hollis, Chris
<x xml:space="preserve">Abstract</x> Background Routine outcome measurement (ROM) in CAMHS is supported by U.K. Government policy. However, little is known about how measures are used in practice. Method Data describing use of ROM, knowledge and attitudes regarding implementation were collected using a regional case‐note audit, online survey and stakeholder workshop. Results While the principle of ROM was supported by stakeholders, baseline and follow‐up outcome measurement occurred in less than a fifth of cases. Barriers to implementation included lack of training and resources, clinicians' perceptions of the limitations of existing measures and lack of regular feedback of outcome data. Conclusions Implementation of ROM may be facilitated by session‐by‐session measures with immediate feedback to clinicians and patients.